Analisis Kegagalan Afghanistan Dalam Eliminasi Kasus Honor Killing Tahun 2011-2018 - Purwati, Ni Kt Rai; Priadarsini, Ni Wayan Rainy; Kumala Dewi, Putu Ratih (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2021)
This study aims to analyze the causes of the failure of the Government of Afghanistan in eliminating honor killings in Afghanistan. This research uses qualitative methods with literature study and secondary data. Honor killings are killings of women for sake of honor whose actions are planned and the execution involves family members. The Afghan government failed to eliminate the honor killing case because after Afghanistan ratified CEDAW in 2003 and passed the 2009 EVAW law relating to the elimination of all forms of discrimination for women, cases continue to increase. Therefore, the author uses the framework of radical feminism and cultural violence to answer the causes of Afghanistan's failure to eliminate honor killings in Afghanistan. This research then found the answer that Afghanistan failed in eliminating honor killings because it was caused by the existence of patriarchy (male domination influenced by the Taliban) and cultural violence in Afghanistan. Keywords: Afghanistan, Cultural Violence, Honor killing, Radical Feminism.